Links and Experience Between Institutions, Industries and Local Community - Olanrele, Olanike Funmi; Ronke, Awodoyin Iyabo (Mediterranean Journal of Social Sciences, 2011)
The desire of the Federal Republic of Nigeria to emerge from her current position to a position of greater height withother developed countries prompted her to adopt education as an instrument per excellence for development. But due toenormous demand of educational institutions which exceed government budget allocation for educational sector, governmentsees it wise to involve the community and others in the establishment of schools. Federal republic of Nigeria through herNational Policy on Education (2004:22) state that ‘government welcomes the participation of voluntary agencies, communities,private individuals, and public organization in the establishment of schools…’ This formed the basis for this paper and thus itexamined historical background of knowledge industries; links between school and community; the conditions for successfultransfer between institutions industries and local community, and benefits to the institutions and community.